Jogos teatrais: uma experimentação com adolescentes da Escola de Teatro e Dança da UFPA no ano de 2015 - NASCIMENTO, Maria Rafaelle Siqueira do (2021)
This job search within the theatrical game universe address the formation of knowledge generated by them within the rehearsal room of the Children and Youth Theatre Group of UFPA, presenting the main contributions of the use of games for the teenagers of the group. It is intended to understand that theater games are provided with contributions to a more comprehensive training of individuals who experience them, and through a theoretical analysis and practical experience highlight freedom, self-confidence, autonomy, community and knowledge of techniques in the theatrical language, and to arrive at these results the applied methodology was participant observation, in which the researcher participates directly in the activities throughout the course of observation, its main theoretical foundations in the generation of arguments of this study some authors, among them: Viola Spolin (2008), Ingrid Koudela (2006) and FaygaOstrower (2008) aimed at theatrical games and process of collective creation through the game. As a result of the research it was found that the use of theater games in the scenic experimental space provides sources of personal freedom, self-expression and autonomy, and promote knowledge and resourcefulness of theatrical language.